2013
DOI: 10.1371/journal.pone.0062790
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Mitotic Recombination within the Basidia of a Hybrid Cross of Cryptococcus neoformans

Abstract: In the majority of diploid eukaryotes, each meiotic process generates four haploid gametes with each containing a single recombinant nucleus. In some species and/or some meiotic processes, aneuploid or diploid gametes can also be generated due to chromosomal non-disjunction and/or the co-packaging of two of the four haploid nuclei into the same gamete. Here we show that another process is involved in generating genotypes of sexual progeny from a hybrid cross between two divergent lineages of the human fungal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 28 publications
6
46
2
Order By: Relevance
“…In a recent study of progeny from AD hybridization, the authors found that more than four haplotypes are present among progeny dissected from a single basidium, which contradicts the principle that one meiotic event can produce a maximum of four genotypes in each basidium. The authors proposed that, post-meiotic mitotic recombination within aneuploid/diploid basidiospores is the reason for the observation of greater than four haplotypes during AD hybridization (Vogan et al, 2013). During both a -α bisexual and α-α unisexual reproduction in serotype D C. neoformans , we also found evidence suggesting that mitotic recombination occurs at a fairly high frequency, and in this case, most likely after karyogamy and prior to meiosis.…”
Section: Recombination During Bisexual and Unisexual Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study of progeny from AD hybridization, the authors found that more than four haplotypes are present among progeny dissected from a single basidium, which contradicts the principle that one meiotic event can produce a maximum of four genotypes in each basidium. The authors proposed that, post-meiotic mitotic recombination within aneuploid/diploid basidiospores is the reason for the observation of greater than four haplotypes during AD hybridization (Vogan et al, 2013). During both a -α bisexual and α-α unisexual reproduction in serotype D C. neoformans , we also found evidence suggesting that mitotic recombination occurs at a fairly high frequency, and in this case, most likely after karyogamy and prior to meiosis.…”
Section: Recombination During Bisexual and Unisexual Reproductionmentioning
confidence: 99%
“…In hybridization between serotypes A and D, elevated sequence divergence and the presence of chromosomal rearrangements serve to repress meiotic recombination, and as a consequence, meiosis is compromised and the majority of hybrid progeny are aneuploid (Sun and Xu, 2007; Sun and Xu, 2009; Vogan et al, 2013). On the other hand, repression of meiotic recombination at certain chromosomal regions could also be beneficial, such as the MAT locus, where crossing over within could result in abnormal chromosomes due to chromosomal rearrangements between the opposite alleles, or non-functional MAT alleles by breaking up co-adapted alleles.…”
Section: Recombination During Bisexual and Unisexual Reproductionmentioning
confidence: 99%
“…In a recent study of hybridization between serotypes A and D in C. neoformans , the authors found that more than four haplotypes could be identified among progeny dissected from one single basidium (Vogan et al, 2013). This contradicts the paradigm that only one meiosis occurs within the basidium, which produces a maximum number of four different meiotic progeny (Idnurm, 2010).…”
Section: Generation Of Genetic Diversity Through Sexual Reproductimentioning
confidence: 99%
“…This contradicts the paradigm that only one meiosis occurs within the basidium, which produces a maximum number of four different meiotic progeny (Idnurm, 2010). The authors proposed that the observed excessive haplotypes from a single basidium are the result of post-meiotic mitotic recombination within aneuploid/diploid progeny that are frequently produced during A-D hybridization (Vogan et al, 2013). Evidence of mitotic recombination has also been found in study of intra-serotype a -α bisexual and α-α unisexual reproduction in serotype D C. neoformans (Sun et al, 2014).…”
Section: Generation Of Genetic Diversity Through Sexual Reproductimentioning
confidence: 99%
“…deneoformans species hybrid” instead of “AD hybrids” or “VNIII” will be impractical to use for the strains with such frequency. Furthermore, the identification of AD hybrids by MALDI-TOF mass spectrometry has been inconsistent (14), and we also do not know whether the MALDI-TOF protein profiles of AD aneuploid/diploid hybrids are distinguishable from the homoploid hybrids (34, 36, 37) formed by mating between VNI (new name, C. neoformans ) and VNIV (new name, C. deneoformans ) strains. Though recombinant haploids are infrequent, recent MLST studies have identified putative recombinant haploids formed between VNI strains and VNIV strains among clinical and environmental isolates (38).…”
Section: Disadvantages In Adopting the New Classification System At Tmentioning
confidence: 99%